Crude Protein and Fiber of Rice Straw Amofer plus Local Microorganims Based on Tomato Waste and Glucose Source: Protein dan Serat Kasar Amofer Jerami Padi yang Ditambah Mikroorganisme Lokal Berbasis Limbah Tomat dan Sumber Glukosa - Handoyo, Erik; Hindratiningrum, Novita; Luthfi, SAC.; Fitria, Restuti (BPFP Universitas Bengkulu, 2025)
By adding tomato waste MOL starter, the purpose of this study is to ascertain the crude protein and crude fiber content of rice straw amofer which is added with different sources of glucose (brown sugar and molasses) and compare it with EM-4. A Complete Randomized Design (CRD) with four treatments and repeated five times was used in the study. The treatmens applied were P0: control was the treatment that was used (without adding starter); P1: incorporating brown sugar and tomato waste MOL starting; P2: adding tomato waste MOL starter with the addition of molasses, P3: adding EM4. The data obtained were analyzed by analysis of variance and followed by Duncan's multiple region test (DMRT) if there were differences in treatment. The variable observed in this study were crude protein and crude fiber. The results showed that the treatment had a significant effect (P<0.05) on the crude protein and crude fiber content. Further DMRT tests showed the highest crude protein and the lowest crude fiber was P0 and if it was compared to other treatments significantly different (P<0.05). The conclusion is that the addition of tomato MOL and EM-4 starters has not been able to increase crude protein levels and reduce crude fiber due to the limited energy contained in the substrate.